New and effective proline-based catalysts for asymmetric aldol reaction in water. Issue 1 (2nd January 2017) - Yorulmaz, Tugba; Aydogan, Feray; Yolacan, Cigdem
ABSTRACT: New proline diamide organocatalysts with Pro-Phe peptide bonds were synthesized and their catalytic activities in asymmetric direct aldol reactions of aliphatic ketones with aromatic aldehydes were investigated. Catalyst6a showed good enantioselectivity at 0 °C in the presence of p-nitrobenzoic acid as cocatalyst in water. GRAPHICAL ABSTRACT: